A COMPREHENSIVE SURVEY ON DETECTING BLACK HOLE ATTACK IN MOBILE AD-HOC NETWORK (MANET) - Pascal Maniriho; Maurice Ntahobari; Radityo Anggoro (JUTI: Jurnal Ilmiah Teknologi Informasi, 2018)
The infrastructure-less nature and mobility of nodes in mobile ad-hoc network (MANET) make it to be very susceptible to various attacks. Besides, owing to its flexibility and simplicity, there is no predefined time or permission set for nodes to leave or join the network and each node can act as a client or server.  Nevertheless, securing communication between nodes has become a challenging problem than in other types of network. Attacks in MANET range into different categories. Black hole attack is one of the attacks that has been addressed by many researchers in the recent years. It does occur when a harmful mobile node called black hole becomes a part of the network and tries to use its malicious behaviors by sending fake route reply packets (RREP) for any received route request packets (RREQ). When these faked packets arrive to the source node, it does reply to them by sending data packet via the established route. Once the packets are received by the black hole, it drops them before reaching the destination.  Hence, preventing the source node from reaching the intended destination. In this paper, we present an overview of a wide range of techniques suggested in the literature for detecting and preventing black hole attacks in mobile ad hoc network. Additionally, the effect of each approach on the network performance is also presented.